Comparative Study of Traditional and Digital Approaches in Qira’ah Learning: A Qualitative Analysis of Students’ Experiences and Comprehension - Marthania Aulia; Tazkya Nurul Aini; Ahmad Nur Mizan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to qualitatively compare the implementation of traditional and digital approaches in teaching Arabic Qira’ah (reading) skills to students of Arabic Language Education. This research employs a qualitative approach with a comparative case study design. The subjects were 20 fourth-semester students of the Arabic Language Education Program at UIN Raden Intan Lampung. Data collection was conducted through participatory observation over 8 sessions, semi-structured interviews, document analysis (field notes and student work), and a reading comprehension test as supporting data. Data analysis followed the Miles, Huberman, and Saldaña model through data condensation, data display, and conclusion drawing. The results indicate that the digital approach excels in learning motivation, autonomy, speed of meaning access, and inferential comprehension but is weak in mastering in-depth grammatical analysis (i‘rab). Conversely, the traditional approach produces more meticulous grammatical understanding and appreciation of classical texts but tends to be monotonous and slow. This study concludes that both approaches complement each other; therefore, an integrative model (blended learning) is the primary recommendation. The implications include the need to redesign the Qira’ah curriculum based on a balance between digital literacy and mastery of classical grammar.